(untitled) (Human Factors in Design, 2021)
The digital magazine market is still consolidating in the midst of the printed model crisis, and it is necessary to understand the reader in this context. The objective is to relate usability and its impacts in the adoption of the digital platform, starting from the perception of the use of a digital newsstand system by exclusively analog readers. The exploratory and descriptive study is part of a usability evaluation process in which 20 exclusively analogue users divided into 2 age groups performed tasks, answered questionnaires and went through an interview using a digital newsstand. The impacts of 15 usability parameters were analyzed, demonstrating their influences on the perception of use and as factors of adoption of the product. Of these, only 3 (Effort, Screen and Terminology) had a greater impact on the positive perception of use, concluding that the current systems need to evolve in several aspects related to usability so that the digital version is more attractive for analogue users. The knowledge generated can be applied both to the development and improvement of systems with similar purposes.